(untitled) (International Conference on Computers in Education, 2020)
The purpose of the current study is to explore the development of high school students’ ICT-related competencies by redesigning a compulsory course for science and technology innovation. Results showed that the course has been implemented successfully. And the teachers teaching behaviors, students learning style, the classroom communication atmosphere, and the after- class evaluation have been positively changed.